Experimental and computational modal analysis of a linear machine axis. (2022) - Holl, Helmut J.; Simader, Victoria; Brandl, Andreas; Hörl, Matthias
Abstract: The mechanical model of a production machine with a moving working tool is a complex dynamic system. The operating parameters have to be determined so that vibrations and deformations are kept small. The suitable behavior of the machine is necessary as it determines the quality of the product. A dynamic model of the production machine can be divided into different sub-models in order to get additional insight to the local behavior and the coupling of different parts of the machine. Suitable simplifications are necessary to get a mechanical model which allows an accurate and efficient simulation. The linear machine axis and the influence of the position of a body mass connected to this axis are studied in such a sub-model in detail. An experimental modal analysis of this sub-system is carried out in order to identify the eigenfrequencies and the eigenmodes. The results of the experiments are compared and evaluated with a computational model which is combined with an analytical model. A modified shape function is derived for the beam model using the measurement data.